Family resilience: a review on articles in spanish - Bravo A., Héctor (2015)
The current article presents a thematic review about the state of the art on family resilience articles published in spanish. Starting from the risk and protective factors, it moves toward a definition of resilience, as well as the emergence of the construct. Besides, there are described the components of the resilience approach, such as the salutogenic and ecological models and positive psychology. Family resilience is characterized from the systemic approach and the family stress theory, as well as the main family resilience processes. Is argued on the relevance of the model to approach to topical issues. Various publications are reviewed by types of study: cualitative and cuantitative researches, and review articles. Conclusions and recomendations emanating from the thematic review are presented to finish.